Maternal oral health status and preterm low birth weight at Muhimbili National Hospital, Tanzania: a case-control study - Manji Karim P; Mumghamba Elifuraha GS (BMC, 2007)
Abstract Background The study examined the relationship between oral health status (periodontal disease and carious pulpal exposure (CPE)) and preterm low-birth-weight (PTLBW) infant deliveries among Tanzanian-African mothers at Muhimbili National Hospital (MNH), Tanzania. Methods A retrospective case-control study was conducted, involving 373 postpartum mothers aged 14-44 years (PTLBW - 150 cases) and at term normal-birth-weight (TNBW) - 223 controls), using structured questionnaire and full-mouth examination for periodontal and dentition status. Results The mean number of sites with gingival bleeding was higher in PTLBW than in TNBW (P = 0.026). No significant differences were observed for sites with plaque, calculus, teeth with decay, missing, filling (DMFT) between PTLBW and TNBW. Controlling for known risk factors in all post-partum (n = 373), and primiparaous (n = 206) mothers, no significant differences were found regarding periodontal disease diagnosis threshold (PDT) (four sites or more that had probing periodontal pocket depth 4+mm and gingival bleeding ≥ 30% sites), and CPE between cases and controls. Significant risk factors for PTLBW among primi- and multiparous mothers together were age ≤ 19 years (adjusted Odds Ratio (aOR) = 2.09, 95% Confidence interval (95% CI): 1.18 - 3.67, P = 0.011), hypertension (aOR = 2.44, (95% CI): 1.20 - 4.93, P = 0.013) and being un-married (aOR = 1.59, (95% CI): 1.00 - 2.53, P = 0.049). For primiparous mothers significant risk factors for PTLBW were age ≤ 19 years (aOR = 2.07, 95% CI: 1.13 - 3.81, P = 0.019), and being un-married (aOR = 2.58, 95% CI: 1.42 - 4.67, P = 0.002). Conclusions These clinical findings show no evidence for periodontal disease or carious pulpal exposure being significant risk factors in PTLBW infant delivery among Tanzanian-Africans mothers at MNH, except for young age, hypertension, and being unmarried. Further research incorporating periodontal pathogens is recommended.